Significant Association Between XRCC1 Expression and Its rs25487 Polymorphism and Radiotherapy-Related Cancer Prognosis - Gong, Li; Luo, Ming; Sun, Renhuang; Qiu, Li; Chen, Chunli; Luo, Zhiguo (Frontiers in Oncology, 2021)
Background/Aims: XRCC1 (X-ray repair cross-complementing protein 1) expression and its single nucleotide polymorphism XRCC1 rs25487 (G>A) may be related to radiotherapy-related cancer prognosis or radiation-induced side effects. However, this association is controversial. We performed a bioinformatic analysis and a meta-analysis to obtain comprehensive results. Methods:TCGA datasets and eligible publications published before November 31, 2020 were retrieved by searching the PubMed, Web of Science and CNKI (China National Knowledge Infrastructure) databases. ORs (odds ratios) and HRs (hazard ratios) with their corresponding 95% CIs (confidence intervals) were calculated to evaluate associations. For XRCC1 single nucleotide polymorphisms, we employed three types of comparisons: GA vs GG, AA vs GG and GA+AA vs GG. Results: Sixty nine articles with 10232 patients and 17 TCGA datasets with 2705 patients were included in the analysis. We observed that high XRCC1 expression was associated with an increased risk of minor treatment response and poor overall survival, XRCC1 rs25487 was associated with reduced risk of minor treatment response in esophageal cancer and an increased risk of high-grade side effects in head and neck cancer. Conclusion: The results suggest that XRCC1 expression and rs25487 polymorphism are prognostic factors for patients receiving radiotherapy-related treatment. Considering the insufficient treatment parameters provided and the various sample sizes in most of the studies, we suggest that genetic association studies related to radiation-based treatment should include more cancer types with suffficient statistical power and more detailed clinical parameters.